Simplified laparoscopic cholecystectomy with two incisions - Rafael Antoniazzi ABAID; Ivan CECCONELLO; Bruno ZILBERSTEIN (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2014)
BACKGROUND: Laparoscopic cholecystectomy has traditionally been performed with four incisions to insert four trocars, in a simple, efficient and safe way. AIM: To describe a simplified technique of laparoscopic cholecystectomy with two incisions, using basic conventional instrumental. TECHNIQUE: In one incision in the umbilicus are applied two trocars and in epigastrium one more. The use of two trocars on the same incision, working in "x" does not hinder the procedure and does not require special instruments. CONCLUSION: Simplified laparoscopic cholecystectomy with two incisions is feasible and easy to perform, allowing to operate with ergonomy and safety, with good cosmetic result.